Estimation of the Thyroid Equivalent Doses to Residents in Areas Affected by the 2011 Fukushima Nuclear Disaster Due to Inhalation of 131I Based on Their Behavioral Data and the Latest Atmospheric Transport and Dispersion Model Simulation. Issue 2 (February 2022) - Kim, Eunjoo; Igarashi, Yu; Hashimoto, Shozo; Tani, Kotaro; Kowatari, Munehiko; Ishikawa, Tetsuo; Kurihara, Osamu
Abstract : Abstract: It has been challenging to obtain reliable estimates of thyroid equivalent doses (TEDs) to residents involved in the 11 March 2011 Fukushima Daiichi Nuclear Power Plant (FDNPP) accident because of the shortage of direct human measurements associated with 131 I, the largest contributor to the dose of concern. The present study attempted to perform the estimation of the TEDs by inhalation of 131 I to residents from Namie-town, one of the most radiologically-affected municipalities, by means of the latest atmospheric transport and dispersion model (ATDM) simulations with the Worldwide version of System for Prediction of Environmental Emergency Dose Information (WSPEEDI) ver. 2, coupled with personal behavioral data containing the history of the whereabouts of individuals shortly after the accident. We analyzed 1, 637 residents who underwent direct measurements with whole-body counters several months after the accident and provided their personal behavioral data. We divided the subjects into two groups based on whether the distances between their locations and the FDNPP were >20 km as of 15:00 on 12 March in relation to the timepoint of the hydrogen explosion at the Unit 1 Reactor building. As a result, the 90th percentile TEDs of the 1, 249 prompt evacuees and 388 late evacuees were 3.9 mSv (adult)–6.8 mSv (10-y-old) and 24.1 mSv (adult)–35.6 mSv (5-y-old), respectively, excluding 16 persons whose TEDs exceeded 50 mSv. The 90th percentile (median) TEDs to 1-y-old children (not included in the subjects) for the prompt and late evacuation groups were 8.1 (1.0) mSv and 36.3 (19.7) mSv, respectively. Additionally, this study provided the evidence to support the view that the explosive event at the Unit 1 Reactor building on the afternoon of 12 March 2011 could have caused the critical group among Namie-town's residents, whereas the largest release event on 15 March gave relatively small doses to the residents because their exposure took place mostly at sites that were distant from the FDNPP. However, the present dose estimation has potentially large uncertainty at the individual level; further validations are thus necessary. Abstract : Supplemental digital content is available in the text.